Real time implementation of embedded devices as a security system in intelligent vehicles connected via Vanets - Senthilnathan Palaniapan; Mohammed Ahsan Kollathodi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The fast boom of  technology has made our lives easier. The number of computer based functions embedded in cars have multiplied extensively over the past two decades. These days, many embedded sensors allowing localization and verbal exchange are being advanced to enhance reliability, protection and define new exploitation modes in intelligent guided transports. An in-car embedded electronic architecture is a complex setup machine, the improvement of that particular system is related to unique manufacturers and providers. There are several factors required in an efficient and secure system along with protection features, real time monitoring, reliability, robustness, and many other integrated features[1-2]. The appearance of modern era has also expanded the use of vehicles and  its associated dangers. Dangers and the road accidents take place often which causes loss of lives and assets due to the bad emergency centres, lack of safety features and limitations within devices embedded within a vehicle.  A rpm-speed calculating device can be used in a vehicle such that risku situations while driving can be detected. A system with Ultra sonic sensor can be used as a crash detector of the automobile in the course of the event and also after a crash. With indicators from the device,  extreme coincidences also can be recognized. .As the amount of urban automobile grows automobile theft has become a shared difficulty for all citizens. As a solution an antitheft system can be implemented using PIR motion sensors where the system can be attached to the peripheral surface of the vehicle. When these sensors are interfaced with  Arduino microcontroller an efficient and reliable security system can be developed[3].